Ko-infeksi asimptomatik helminthiasis pada pasien tuberkulosis paru di Surabaya kota: studi pendahuluan - Rifat Nurwita Kusumaningtyas; Indah Setyawati Tantular; Deby Kusumaningrum; Rina K Kusumaratna (Jurnal Biomedika dan Kesehatan, 2020)
BACKGROUNDPulmonary tuberculosis (TB) is a leading cause of morbidity and mortality, and East Java province is the second largest contributor of co-infection in Indonesia. Asymptomatic helminth infection among pulmonary tuberculosis patients causes another public health problem. Few data relate to helminth infection based on clinical and immunological outcomes of pulmonary TB in highly endemic areas. METHODSThis study was designed as a preliminary study and aimed to determine helminth co-infection among TB patients with a macroscopic assessment. This cross-sectional study was conducted in June-August 2017. RESULTSAmong 16 treated active TB patients from TB cohort data of Tanakali Kedinding health center found that 56% were stool smear-positive for Trichuris trichiura eggs, but had no clinical symptoms. CONCLUSIONWhether or not the helminth infection may have an impact on the diagnosis and treatment of active TB remains to be further investigated. Co-infection could be inhibited by the host immune response and improve the prognosis of TB treatment.